PENGARUHI PROFITABILITAS, STRUKTUR MODAL, NILAI PERUSAHAAN DAN LIKUIDITAS TERHADAP NILAI PERUSAHAN (Studi Pada Perusahaan Asuransi di Bursa Efek Indonesia Tahun 2010-2013) - Wulansari, Tri; Herawati, Juni (Jurnal Ilmiah Mahasiswa FEB, 2016)
The creation of firm value can provide a positive impact to the owner of the company or shareholders. The purpose of this research is to examine the influence of provitability which is proxied to return on assets (ROA), capital structure which is proxied to debt to equity ratio (DER), firm size and liquidity which is proxied to current ratio (CR) to the firm value which is proxied to price-book value (PBV). The population in this study is a insurance company on the Indonesia Stock Exchange during the period 2010 to 2013. Samples were taken by all of company in this population as much as 10 company. Processing and testing data using Software Statistical Product And Service Solution versi 20.0. Tested in this study used multiple regression analysis. From the results of multiple regression analysis known that profitability, capital structure, firm size and liquidity simultaneously affect firm value. Profitability has positive effect, significant variabel on firm value. Capital structure and firm size variabel has negative effect and non significant on firm value.. Whereas in Liquidity has negative effect and significant on firm value. Â  Keywords: Profitability, Capital Structure, Firm Size, Liquidity, Firm Value